Health-seeking behaviour and delayed presentation of oral cancer patients in Malaysia: A qualitative study / Nurizyani Azhar - Nurizyani, Azhar (2017)
Objective: The aim of this study was to explore the pattern of health-seeking behaviour among oral cancer patients in Malaysia and identify behaviours that lead to their delayed presentation. Method: A qualitative exploratory study was carried out using semi-structured in-depth interviews among 35 oral cancer patients having disease stages ranging from TNM stage III to IV, who were treated at six tertiary regional centres managing oral cancer throughout Peninsula Malaysia, Sabah and Sarawak. A focus group discussion was carried out for a methodological triangulation purposes. All interviews were audiorecorded, transcribed verbatim and coded using NVivo (version 10.0) qualitative software. The coding process was based on the priori themes of the Self-Regulatory Model’s components which were; participants’ symptom interpretations, coping strategy and their appraisal of coping efforts. All transcribed verbatim from both semi-structured in-depth interviews and focus group discussion were analysed using framework analysis. Results: 35 participants tended to interpret their early disease signs and symptoms as a minor condition and did not consider it as requiring immediate attention. This was found to be one reason for the delay in presentation at the clinic. Those from a low education background failed to interpret their symptoms. Participants were unconcerned about its presence, most likely due to a lack of knowledge and awareness regarding oral cancer. Four main types of coping procedures which accounted for patients’ delay in seeking help emerged: 1) self-remedy 2) self-medication using unconventional medicine; 3) seeking traditional healers/medicine and 4) consulting general medical practitioners (private sector) instead of the dentists. Participant-related factors such as socio-demographic characteristics (age, gender and residential area), socio-economic status, cultural beliefs and religious practices influenced delay in seeking help among oral cancer patients in iv Malaysia. Smoking, excessive alcohol consumption and betel quid did not influences participants’ health-seeking behaviour due to their limited knowledge regarding these high-risk habits that may be a contributing factor of oral cancer. Participants’ preference to seek private sector general medical practitioners as their first options of seeking care (due to lack of knowledge) was one other reason for prolonged delay in diagnosis that may lead to professional delay. A health-seeking pathway was constructed based on the data (adapted from the Self-Regulatory Model) to show participants’ pattern of seeking care. The emergent themes such as (i) misdiagnosis by healthcare professionals due to ‘incorrect history provided by participants’, ‘doctor’s lack of awareness regarding early sign and symptom of oral cancer’ and ‘poor doctor-patient’s communication’ led to a professional delay in the present study. Moreover, the (ii) availability and accessibility of cheaper over-the-counter medicines in pharmacies were found associated with participants delay in diagnosis. Conclusion: Participants low levels of public knowledge and awareness regarding oral cancer as well as their psychological factors were found to influence their health-seeking behaviour in terms of symptom interpretation, coping strategy and appraisal of coping efforts which resulted in their delay in seeking help and being diagnosed early. General medical practitioners’ inability to detect early signs of oral cancer led participants to experience a professional delay.